Effect of Cooking on Isoflavones, Phenolic Acids, and Antioxidant Activity in Sprouts of Prosoy Soybean (Glycine max). Issue 7 (3rd June 2016) - Kumari, Shweta; Chang, Sam K. C.
Abstract: Soy sprouts possess health benefits and is required to be cooked before consumption. The effects of cooking on the phenolic components and antioxidant properties of soy sprouts with different germination days were investigated. A food‐grade cultivar Prosoy with a high protein content was germinated for 1, 2, 3, 5, and 7 d and cooked till palatable for 20, 20, 5, 5, and 7 min, respectively. Total phenolic content (TPC), total flavonoids content (TFC), condensed tannins content (CTC), individual phenolic acids, isoflavones, DPPH, ferric‐reducing antioxidant power (FRAP), and oxygen radical absorbance capacity (ORAC) of raw and cooked sprouts were measured. Cooking caused significant losses in phenolic content and antioxidant activities, and maximum loss was on day 3 > 5 > 7, including TPC (32%, 23%, and 15%), TFC (50%, 44%, and 20%), CTC (73%, 47%, and 12%), DPPH (31%, 15%, and 5%), FRAP (34%, 25%, and 1%), and ORAC (34%, 22%, 32%), respectively. Cooking caused significant losses in most individual phenolic acid, benzoic group, cinnamic group, total phenolic composition, individual isoflavones, and total isoflavones. The losses of phenolic acids such as gallic, protocatechuic, hydroxybenzoic, syringic, chlorogenic, or sinapic acids during cooking were not compensated by the increases in trihydroxybenzoic, vanillic or coumaric acids on certain days of germination. Cooking caused minimal changes in phenolic acid composition of day 1 and 2 sprouts compared to 3, 5, and 7 d sprouts.